Cycles of Accumulation and Industrial Slowdown in Malaysia: Rents, Social Forces and the Political Settlement. Issue 2 (15th March 2021) - Tan, Jeff
ABSTRACT: This article seeks to explain the failure of industrial upgrading in Malaysia in terms of the state's capacity to allocate and manage rents to promote learning and accumulation, and to withdraw rents associated with political accommodation. It introduces the cycle of accumulation as a framework to examine evidence of how the allocation of rents affects the pattern of accumulation and emerging social forces. These social forces in turn influence the political settlement and subsequent allocation of rents. In contrast to a focus on elites and elite motivation, this article argues that state capacity is affected by the state's connections with both elites and non-elite social classes and groups.